Integroup reconciliation: The „unbearable lightness“of saying, the unbearable heaviness of doing it - Čorkalo Biruški, Dinka (2011)
The paper presents results of 10 years of research of the social reconstruction processes in the postconflict community in the city of Vukovar, Croatia. Recommendations for the intergroup rapprochement in the post-conflict community are given and theoretical and practical implications are discussed.